Roles of LRRK2 and its orthologs in protecting against neurodegeneration and neurodevelopmental defects - Nguyen, An Phu Tran; Nguyen, Linh Thi Nhat; Stokke, Bailey A.; Quinn, Christopher C. (Frontiers in Cell and Developmental Biology, 2025)
In humans, variants in the LRRK2 gene are the most prevalent risk factors for Parkinson’s disease (PD). Whereas studies in model organisms have long indicated that the orthologs of the wild-type LRRK proteins protect against neurodegeneration, newer findings indicate that they also protect against neurodevelopmental defects. This normal role of the LRRK proteins can be disrupted by either gain-of-function (GOF) or loss-of-function (LOF) mutations, leading to neurodegeneration and neurodevelopmental defects. Here, we review the roles of the LRRK proteins and their orthologs in these processes, with a focus on autophagy as a common factor that may mediate both of these roles. We also highlight the potential for experiments in vertebrate and invertebrate model systems to synergistically inform our understanding of the role of LRRK proteins in protecting against neurological disorders.